Computational modelling of copolymers using a phase field approach - Kay, D; Styles, V; Münch, A; Parsons, Q (AIP Publishing, 2020)
In this work we will present a practical computational scheme for a phase field approximation of the Ohta–Kawasaki type for multiple block copolymers. The phase field model presented will be shown to be computationally.